All Days 2000
DOI: 10.2118/58789-ms
|View full text |Cite
|
Sign up to set email alerts
|

Borehole Failure: Safe Drawdown Pressures and Wellbore Damage Radius

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThis paper addresses the problem of onset of failure and the subsequent development and propagation of the failed (or plastic) zone during production. It uses an elasto/plastic formulation 1 to find the distance of the damaged radius for cased and uncased wells. Numerical examples and laboratory tests are used to show the onset of failure and the growth of the plastic zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Furthermore, by the adoption of optimum deviation angle and drilling direction, it is shown that the mechanical stability of inclined wells can be increased. The work in Morales et al presents numerical examples and laboratory tests to show the onset of failure and the growth of the plastic zone development and propagation during production. In Wanga and Dusseault, a method is proposed for the calculation of linear thermo‐poroelastic tangential stresses around a borehole, in a medium with isotropic permeability for the case of constant borehole temperature and variable pore pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by the adoption of optimum deviation angle and drilling direction, it is shown that the mechanical stability of inclined wells can be increased. The work in Morales et al presents numerical examples and laboratory tests to show the onset of failure and the growth of the plastic zone development and propagation during production. In Wanga and Dusseault, a method is proposed for the calculation of linear thermo‐poroelastic tangential stresses around a borehole, in a medium with isotropic permeability for the case of constant borehole temperature and variable pore pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Bottomhole pressure also controls the effective stress born by the formation that will have an impact on formation collapse and sand production. Studies have shown that for wells with no sand-exclusion device preventing sand ingress, a critical pressure exists, below which sand failure and sand production are expected to occur (Morita et al 1989;Zhang et al 1998;Morales et al 2000). Permeability can decline because of compaction; therefore, bottomhole pressure may also have a large impact on the formation permeability near the wellbore.…”
mentioning
confidence: 99%